Mediating EffectofStudentsEntrepreneurialAttitude inRelationshipofFinancialLiteracyandFinancial BehavioronEntrepreneurialIntention (Journal of Asian Development Studies, 2024)
Entrepreneurship is often regarded as a significant driver of economic development due to its ability to provide employment opportunities and viable resolutions to societal challenges. This research aims to determine the impact of financial behavior and literacy on entrepreneurial intention, specifically among business administration students who are the participants of this study in Sindh universities. Furthermore, the present study also investigated the extent of financial literacy and financial behavior among business administration students at the Sindh University Campus in Larkano, Pakistan. The present study utilizes a quantitative methodology, with data being gathered via the administration of a survey questionnaire. The research revealed a significant and favorable correlation between financial literacy and the financial behavior of business students, as well as their intention to start their firms. The results also highlight the connections between financial behavior, entrepreneurial attitude, and entrepreneurial intention, and pointing to the student entrepreneur's attitude does not mitigate the direct impact of financial behavior on entrepreneurial intention. This implies that how people handle their financial matters directly influences their intention to engage in entrepreneurial activities, irrespective of their attitude towards entrepreneurship. The findings underline the significance of developing healthy financial habits as a prerequisite to developing entrepreneurial intention